CORPORATE GOVERNANCE, CAPITAL STRUCTURE, AND CORPORATE INVESTMENT: AN EMPIRICAL STUDY ON PROPER MANUFACTURING INDUSTRY IN INDONESIA - Maulina, Gilda; Nuzula, Nila Firdausi; Damayanti, Cacik Rut (Universitas Brawijaya, Indonesia, 2021)
Investment is one of the most crucial decisions that a company must create to achieve higher financial performance and to maintain long-term sustainability. This study predicts that two significant factors determine corporate investment, i.e., the firms' corporate governance and capital structure. The article also assumes that companies that are aware and engage in environmental programs would find it much easier to gain investors'. This study used 39 units of analysis of 13 manufacturers listed on the Indonesia Stock Exchange that received a good ranking in PROPER during the 2016-2018 period and analyzed with structural equation modeling (SEM). This study finds that corporate governance is negatively related to the capital structure but positively related to corporate investment. However, the capital structure does not affect corporate investment implying environmental performance's significance in leading corporate governance and enhancing corporate investment. Further research can extend the observation period, use other sectors as the sample, use the different indicators in each variable, and develop the relationship between variables on a broader framework.